PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL (Studi Empiris Pada PT. Asuransi Jiwa Manulife Indonesia) - Denny Asmas (Universitas Batanghari Jambi, 2014)
The research objective of this study was to determine the effect of budget participation on managerial performance in PT Asuransi Jiwa Manulife Indonesia.Populasi in this study were all branch heads Manulife Financial totaling 150 branches in Indonesia using purposive sampling technique. Head of the branch selected as the study sample because it has a delegation of authority as well as participate in the drafting process anggaran.penelitian conducted using linear regression Budget sederhana.Partisipasi significant positive effect on managerial performance at Manulife Financial, so the hypothesis is proven and to improve managerial performance can be done by increasing the participation of budget. From these results partisipasianggaran metunjukkan that positively affect managerial performance, which means the involvement of all the branch manager at Manulife Financial in Indonesia in the budgetary participation affecting managerial performance.Keywords: Influence, Budget Participation, Managerial Performance